An Observational Study of Grahani Roga as a Lifestyle Disease and its Hetus with Special Reference to Role of Agni: Array - Shete, Arati S.; Nakel, Mahavir Pannalal (Ayurline: International Journal of Research in Indian Medicine, 2019)
Introduction- Grahani Roga is a disease related to the gastrointestinal tract. In the present era of fast food, irregularity in diet, sedentary lifestyle and tremendous mental stress; psychological factors like Kama, Krodha, Shoka etc. leads to Agni Dusti (Mandagni or Vishmagni or Tikshnagni-collectively it is called Grahani Dosha). Aim- To study the Grahani Roga.and its Hetus with special reference to Agni Dushti. Objectives- 1. To assess the role of Agni in Grahani Roga. 2. To study different Hetus associated with Grahani Roga. Methodology- Participants in the adolescent age group with classical sign and symptoms of Grahani Roga (Amavastha), i.e. Muhu Baddha and Drava Mala Pravritti, Apachana, Udara Shoola, etc. were randomly selected. Observations- Out of total study subjects, 81.66% subjects were having weak Jaran Shakti suggestive of Agnimandya. Ati Katu Ahara 76.66 % was the most common factor under Aharaja Nidana causing Agnimandya. In the adolescent age group, people usually do Adhyashana, Vishamashana, Ratrijagaranam,and Diwasvapana, which leads to Tridosha Dushti – mainly Samana Vayu, Pachaka Pitta, and Kledaka Kapha, and also tension or anxiety is prevalent, leading to Agni Dushti and finally, Amavastha of Grahani Roga. Conclusion-Mithya Aahara Vihara is the main cause of the Agni Dushti, which leads to Ama Dosha and finally, it results in Grahani Roga.